Elimination Games: The Global Rise of Military Reality TV and the Shaping of the Citizen Subject - Kaempf, Sebastian; Stahl, Roger (Millennium, 2023)
The past decade has seen the global growth of military-style reality television programming. These programmes, produced by militaries themselves or through collaboration with the entertainment sector, have proven to be an effective and increasingly powerful public relations conduit. Our article offers a theoretical treatment of reality television, both the aesthetic modes by which it invites the viewing subject as well as the political economy of its use in public relations. These dimensions are explored through two case studies. First, we focus on the genesis of military-style reality TV in the United States, where, after 9/11, the US military seized on the genre to pioneer and field-test various themes in response to public exigency as the occupations of Afghanistan and Iraq drew on. Second, we analyse the German military as both a latecomer and innovator to these new public relations endeavours. By reading the generic and aesthetic strategies in both cases, we argue that the genre’s public relations function goes beyond the immediate task of recruitment to cultivate civic participation in militaristic fantasies through a mediasphere rife with invitations to ‘go soldier’. Military reality TV, we argue, represents the militarization of civic identity and the gradual displacement of values from deliberative to authoritarian, cosmopolitan to nationalistic and diplomatic to combative. Jeux éliminatoires : L’essor mondial de la télé-réalité militaire et la formation du citoyen sujet